The effect of sustainable agricultural practices on crop productivity in Ethiopia: insights from a meta-analysis - Ejeta, Tadesse Tolera; Bai, Xiuguang (Frontiers in Sustainable Food Systems, 2025)
Conventional agriculture harms the environment and threatens sustainability. To address these issues, sustainable agricultural practices (SAPs) have become imperative. This study utilizes a meta-analysis approach to comprehensively assess empirical studies, investigate the impact of SAPs on crop productivity, identify influencing factors, and examine their temporal evolution. The findings reveal that (1) SAP adoption significantly and positively influences crop productivity, with multiple practices exhibiting the most substantial impact, followed by sustainable agricultural technology. Individuals who adopted SAPs achieved crop productivity that was 980 kilograms per hectare higher than those who did not. (2) Factors such as age, farm size, family size, livestock units, credit access, off-farm income, market distance, and cooperative membership negatively affect crop productivity, whereas education and extension services have a positive impact. (3) The positive effects of education and extension services on crop productivity strengthen over time. The strengthening of these variables over time implies a gradual increase in farmer awareness, access to resources, and adoption of SAPs, highlighting their evolving role in driving them. Accordingly, none of the past researchers identified any patterns in the variables influencing crop productivity. Therefore, promoting SAP adoption and prioritizing education and extension services can offer farmers with experience and support, thereby enhancing crop productivity. Future initiatives should therefore combine interdisciplinary methods, technology, and community involvement for ensuring SAP’s sustainability and scalability.